Caregivers’ perceived emotional and feeding responsiveness toward preschool children: Associations and paths of influence - Fernandes, Carla (2021)
Although there is a large body of research connecting emotion to eating behaviors, little is known about the role of caregivers’ responses to children’s emotions in the context of child feeding. The purpose of this study was to analyze the relation between caregivers’ emotional responsiveness and feeding responsiveness. The mothers of 137 children between 2 and 6 years of age reported on their responses to children’s negative emotions using the Coping with Children’s Negative Emotions Scale and on their feeding practices using the Comprehensive Feeding Practices Questionnaire. The results showed that mothers’ supportive emotion responses (e.g., problem-focused, emotion-focused, and expressive encouragement reactions) tend to be positively associated with responsive feeding practices (e.g., encouraging, modelling, and teaching healthy food-related behaviors). Instead, mothers’ unsupportive responses (e.g., distress, punitive and minimization reactions) tend to be positively associated with nonresponsive feeding practices (e.g., food as reward or to regulate emotions, and pressure to eat) and negatively associated with responsive feeding practices. Our results suggest that emotional and feeding responsiveness may be intertwined and that differences in parent’s emotional responsiveness may translate into differences in their feeding styles, setting the stage for parents’ use of positive vs. negative feeding practices.